Trajetória, memória, hierarquia e poder Vicente Mariano e o Terreiro Senhor do Bonfim Ilê Oxum Ajamin - Lira, Larissa Sarmento (2017)
The story of a religious space inspires us that is the Terreiro Senhor do Bonfim Ile Oxun Ajamin and the trajectory of a character that marks the life of the religion of the orixas in the city of Campina Grande, the tatalorixa Vicente Mariano. His experience, his pioneering character pertaining to the structuring and the consolidation of a religious space, arouse our attention and are preconditions to think about strategies that contributed to the expansion of the religion in this locality. Vicente tells us that he was initiated in Recife, in a yard of candomblé nagô having Lídia Alves e José Romão da Costa respectively as his mãe e pai de santo (something like an spiritual guide and caretaker). It is through these characters’ perspective that we enter the universe of xangô from Pernambuco. “O Sítio de Pai Adão e o Terreiro de Nação Xambá” are references that helped us map the trajectory that we decided to investigate. This research tries to understand the role of the cleric in the development and configuration of the afro-religious field in Campina Grande. Ethnographic work allowed us, as much as possible, to observe, retrieve, analyze and try to describe the history of the Ile Oxum Ajamin that matches the trajectory of Vicente Mariano, as well as with the history of afro-religious cults in the State of Paraíba. To give a voice to some of the characters involved in the construction of this memory and to enter the universe of their practice aims to contribute to the afro-campinense studies, to lead to the understanding of facts that have marked the development of umbanda-jurema, the formation of candomble nago in the city of Campina Grande, and the influence of the xango pernambucano to afro-religiosity in Paraíba.